Nanomechanics of multiferroic composite nanofibers via local excitation piezoresponse force microscopy. (May 2019) - Zhu, Qingfeng; Pan, Kai; Xie, Shuhong; Liu, Yunya; Li, Jiangyu
Abstract: Mechanical properties of multiferroic nanostructures are of great importance for their applications, yet their characterization is challenging, especially in a quantitative manner and simultaneously with their piezoelectric properties. In this paper, we show that the widely applied piezoresponse force microscopy, when appropriately carried out and analyzed, can be utilized to quantitatively map the Young's modulus of multiferroic nanofibers with high accuracy and spatial resolution, while their piezoelectricity can be simultaneously determined as usual. The analysis is built on three tightly coupled models, one on contact resonance for the dynamic motion of the cantilever, one for quasi-static contact mechanics between the tip and sample, and the third regarding dynamic tip-sample interaction, with which the mechanical properties of the nanofiber can be deduced from the contact resonance spectrum locally excited by the charged probe, taking advantage of the electromechanical coupling of multiferroic composites. Furthermore, two flexural modes of contact resonances are used in combination with reference material for calibration, so that explicit measurement of some critical model parameters can be avoided. We apply the method to Pb(Zr0.52 Ti0.48 )O3 -CoFe2 O4 composite nanofibers with different compositions, and demonstrate its excellent agreement with destructive nanoindentation method, globally excited contact resonance approach, as well as micromechanics rule of mixture. The method can be easily applied to a wide variety of multiferroic nanostructures as well.